Efektivitas E-modul IPA bermuatan SSI dengan Model PBL utk Meningkatkan Keterampilan Berpikir Kritis dan Literasi Sains Peserta Didik SMP - Ni Ketut Heri Kusumaningsih; Ni Made Pujani; I Nyoman Tika (Postgraduate, University of Mataram, 2025)
The limited availability of teaching materials that support the development of critical thinking skills and scientific literacy in a contextual and reflective manner. Textbooks used in schools generally focus on memorizing concepts and do not encourage the exploration of complex socio-scientific issues. This, study aims to test the effectiveness of a science e-module containing Socio-Scientific Issues (SSI) with a Problem-Based Learning (PBL) model in improving critical thinking skills and scientific literacy of junior high school students. The study used a one-group pretest-posttest design as part of the assessment stage in the R&D Plomp model. The research subjects consisted of 44 eighth-grade students of SMP Negeri 2 Singaraja, who were selected purposively. Data were collected through a critical thinking skills test based on Ennis indicators and a science literacy test based on Vision III. The analysis results showed a significant increase in the posttest scores of critical thinking skills (N-Gain = 0.70) and science literacy (N-Gain = 0.58), with a high effect size value. Analysis per indicator showed the highest increase in the Situation and Reason indicators (critical thinking), as well as Critical Thinking and Acting (science literacy). The e-module also encouraged active student involvement in problem-based learning and contextual issues